THE INFLUENCE OF WORK FACILITIES AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT CBC CLINIC BSD BRANCH - Guruh Dwi Pratama; Angga Pratama; Albani Putra Danu (International Journal Management and Economic, 2024)
This research aims to analyze the influence of work facilities and work motivation on employee performance at the CBC Clinic BSD branch. This research uses a quantitative method with an associative approach, where work facilities and work motivation are treated as independent variables, while employee performance is the dependent variable. The population of this study consisted of all employees of the CBC Clinic BSD branch, and the sample used was a saturated sample involving the entire population, namely 30 employees. Data analysis was carried out using multiple linear regression. The research results show that there is no significant influence between work facilities on employee performance at the CBC Clinic BSD branch. This indicates that although existing work facilities may be important for creating a comfortable work environment, these facilities are not enough to directly influence employee performance. Apart from that, the research results also revealed that work motivation did not have a significant influence on employee performance when tested partially. These findings indicate that there are other factors outside of work facilities and motivation that play a more important role in determining employee performance at the clinic. Therefore, it is recommended that the management of the CBC Clinic BSD branch consider a more holistic approach in improving employee performance by paying attention to other factors that may be more significant.